Selection into Entrepreneurship, Income Mobility and Firm Performance - Harju, Jarkko; Juuti, Toni; Matikka, Tuomas (Journal of Labor Economics, 2025)
Using full-population data from Finland, we show that individuals at the top of the income distribution are significantly more likely to start new incorporated businesses. High-income earners also establish more successful and productive businesses than others. In contrast, parental income is not linked with selection into new entrepreneurship or firm-level outcomes. We find that income gains from entrepreneurship are rather similar across individual and parental characteristics, and that entrepreneurship is associated with upward income mobility regardless of initial income levels. Overall, our findings suggest that entrepreneurship can serve as an upward economic ladder for individuals from diverse backgrounds.